A6.21 NF-κB-inducing kinase (NIK) is expressed in synovial endothelial cells in early arthritis patients and correlates with markers of inflammation. (13th February 2015) - Maijer, KI; Noort, AR; de Hair, MJH; van der Leij, C; van Zoest, KPM; Choi, IY; Gerlag, DM; Maas, M; Tak, PP; Tas, SW
Abstract : Background and objectives: The NF-κB family of transcription factors is strongly involved in synovial inflammation. We have previously shown that NF-κB-inducing kinase (NIK) is a key regulator of inflammation-induced angiogenesis in rheumatoid arthritis (RA) synovial tissue (ST). Here, we investigated synovial NIK expression in early arthritis patients and in autoantibody-positive individuals at risk for developing RA. Materials and methods: ST biopsies were obtained via arthroscopy from 154 early arthritis patients (arthritis duration <1 year) with different diagnoses and from 54 IgM-rheumatoid factor and/or anti-citrullinated peptide antibody-positive individuals at risk for developing RA, without any evidence of arthritis. ST was stained for NIK and the endothelial cell (EC) marker vWF. Additionally, measures of disease activity (ESR, CRP, joint swelling) were collected and contrast-enhanced MRI was performed in a subset of these patients. Results: In early arthritis patients, NIK was predominantly expressed in EC of small blood vessels. Furthermore, NIK expression correlated with ESR (r = 0.184; p = 0.024), CRP (r = 0.194; p = 0.017), joint swelling (r = 0.297; p < 0.001), synovial cellular markers (CD68 + lining and sublining macrophages r = 0.585; p < 0.001 and r = 0.728; p < 0.001, respectively, CD3 + T cells r = 0.733; p < 0.001 and CD22 + B cells r = 0.264; p = 0.040), MRI effusion (r = 0.665; p < 0.001), MRI synovitis (r = 0.632; p < 0.001) and MRI total score (r = 0.569; p < 0.001). In 18.5% of autoantibody-positive individuals ST NIK + EC were present, but this was not predictive for the development of arthritis. Conclusions: NIK + EC are present in the earliest phase of synovial inflammation and may be indicative of high angiogenic activity in the inflamed ST. Therefore, NIK + EC may play an important role in the persistence of synovitis. Collectively, our data underscore the importance of angiogenesis in synovial inflammation and identify NIK as a potential therapeutic target in arthritis.